Pemberdayaan Modal Sosial sebagai Model Pencegahan Radikalisme untuk Menciptakan Harmoni Sosial di Bali - Dermawan Waruwu; Made Nyandra; Ni Made Diana Erfiani (Pusat Kajian Bali Universitas Udayana, 2020)
The spread of radicalism has ruined the social, cultural, economic, and harmony between religious believers in Bali. The bombings in Bali on 2002 and 2005, were carried out by people who were exposed to radical understandings, and their acts not only killed innocent people but also destroyed harmonious inter-ethnic relationship in Bali. This article analyzes the form of empowering social capital, as a model for preventing radical understanding to create social harmony in Bali. Data is collected with religious leaders and communities through observations, interviews and documents related to the development of radicalism, terrorism and intolerance in Bali. Data is analyzed qualitatively and examined using social practice theory. The results show social capital in increasing solidarity in terms of diversity, social capital in improving social relations, and social capital in increasing spiritual value. These forms of social capital can be used as models in preventing radicalism in Bali.